Urbanisme civique en temps de crise : Les espaces publics d'Hispanie et de l'Occident romain entre le IIe et le IVe siècle - Quevedo, Alejandro; Brassous, Laurent (Collection de la Casa de Velázquez, 2015)
Articles dealing with the history of cities in the Western Roman Empire from the height of the empire to late antiquity.